SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JUARA KELAS SISWA PADA MI DARUL ULUM 2 BENDUNGREJO MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Anissa Sari, Vicky; Lazulfa, Indana (Inovate, 2023)
Decision support system is a system that can provide problem solving, and can carry out communication forsolving certain problems in a structured or unstructured manner. The decision support system at the MI DarulUlum 2 Bendungrejo school currently only focuses on aspects of academic value. Hence, the determination ofclass champions running less optimally. This research aims to design decision support for determining web-basedclass champions and to apply the Analytical Hierarchy Process (AHP) in the problem of determining classchampions at MI Darul Ulum 2 Bendungrejo. The results of this study are that the Analytical Hierarchy Process(AHP) method can be applied to a decision support system for determining class champions at MI Darul Ulum 2Bendungrejo. The system is able to provide ranking results that are in accordance with several criteria, namelyfinal test scores, midterm test scores, quiz scores and number of absence.Keywords – Decision Support System, class champions, Analytical Hierarchy Process (AHP)